Differences in Fitness Level of Students Studying Basketball and Volleyball in Communication Science Study Program UPN "Veteran" Yogyakarta Batch 2023/2024 - Sumintarsih Sumintarsih; Tri Saptono; Hanafi Mustofa (Eduvest - Journal of Universal Studies, 2025)
The objectives of this research are: 1) Assess the influence of basketball and volleyball on physical fitness levels. 2) Compare the level of physical fitness between female and male students. 3) Assess the differences in the influence of basketball and volleyball on improving the physical fitness of female students. 4) Assess the differences in the influence of basketball and volleyball on improving the physical fitness of male students. 5) Testing the interaction between sports (basketball and volleyball) and gender on increasing physical fitness. The research used an experimental method with purposive random sampling from 6 students per group. Data analysis techniques include the T test, normality test (Kolmogorov-Smirnov), and homogeneity of variance test (Levene's Test). The research results show: 1) Basketball (mean 3.655833333) provides a better increase in physical fitness than volleyball (mean 2.71666666) with a mean difference of 0.939166666. 2) Female students (mean 3.844166667) experienced a better increase in physical fitness than male students (mean 2.528333333) with a mean difference of 0.657916667. 3) Women's basketball (mean 4.686666667) provides a better increase in physical fitness than women's volleyball (mean 3.001666667) with a mean difference of 1.685. 4) Men's basketball (mean 2.625) showed a better increase in physical fitness than men's volleyball (mean 2.431666667) with a mean difference of 0.193333333. 5) There is no significant interaction between sport and gender on increasing physical fitness, with the Fcount (1.45530676) being smaller than Ftable (4.35) at the 5% significance level